Peculiarities of application of the resources of the Moscow Electronic School platform for the formation of language competence of the students of non-linguistic specialties - Tatyana V. Masharova; Ekaterina K. Starkova; Ivan V. Shunin; Anna S. Pastukhova (RUDN Journal of Informatization in Education, 2025)
Problem statement. The modernization of current foreign language training of students necessitates the active usage of digital technologies that simultaneously ensure the development of lexical, grammatical and phonetic skills. However, many informatization tools (for example, Lingvist, Memrise, Quizlet, etc.) are used by teachers only for the development of individual components of students’ language competence (structural or subject-procedural). The article presents a study aimed at identifying the features of using the Moscow Electronic School information educational platform (hereinafter referred to as MES) in order to effectively form the language competence of students of non-linguistic specialties. Methodology. The MES platform is considered as an informational and educational resource that supports the solution of the tasks of individualizing foreign language education and increasing the availability of high-quality education. The central component is an electronic library (a database of multimedia materials). The study involved 174 students (in four training areas) of P.A. Ovchinnikov Polytechnic College. The materials of the author’s testing were used to assess the level of formation of language competence. The χ2 (chi-square) Pearson’s criterion was applied for statistical processing. Results . The MES platform has developed multimedia thematic modules (texts, video and audio clips, illustrations and animations); interactive tasks and exercises for developing language skills; communicative simulators and role-playing games for applying learned language tools in simulated situations of intercultural and professional communication; linguistic and cultural quests and projects that stimulate students to search and creatively process information; interactive dictionaries, glossaries, thesauri. The didactic potential of the MES platform for the formation of linguistic competence of students of non-linguistic specialties has been clarified: the availability of tools to support the development of all components of foreign language communicative competence in the classroom, online, and in individual training; adaptation of developed multimedia materials to different levels and courses of study; integration of previously developed digital resources. Conclusion . The peculiarities of the formation of linguistic competence of students of non-linguistic specialties by means of MES include the following: the development of competence proceeds through the search and resolution of problematic situations supported by texts on special topics and posted on the platform; foreign language activities are aimed at solving tasks designed to assimilate the content of linguistic competence at algorithmic and heuristic levels; for the management of educational and speech skills of self-monitoring and self-assessment activities sets of tasks and tests that require systematic work with the resources of the database of materials are used.